Exploring Project Success Factors in Developing Countries: Focus on Morocco - Asmaa El Mourabit; Abdeslam El Moudden (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Although project management (PM) literature has addressed project success, attention has not been paid to statistically testing the relationship between various critical success factors (CSFs) and project success in developing countries. Determining the most relevant factors can optimize efforts and boost the project success dimension in this specific environment that struggles to achieve the desired development objectives. Therefore, the aim of this paper is to statistically prove the relationship between project success and an extant range of selected CSFs that englobe PM variables, organization structure, project manager competencies, communication, top management, risk management, and prioritize them to provide valuable information to project managers and enhance the likelihood of project success. The data were collected by means of a survey addressed to project managers and practitioners from Morocco in both public and private sector. Multiple stepwise regressions were conducted to uncover the relationship between each success criteria and the considered CSFs. The results show that the considered model for the first factor of project success covers 59,1% of its variance. The significant variables of this model are PM competencies and PM KPI that increase the success of the first factor by 49% and 29%, respectively. The variance of the second factor of project success is explained by 68%. The significant independent variables are communication, top management support, PM Partnership, PM KPI, and PM policy and strategy. According to the results, the variables participate in project success by 37%, 28,1%, 19,8% 29,9% and 15,5%, respectively.